Climatic threshold of crop production and climate change adaptation: A case of winter wheat production in China - Huang, Na; Song, Yu; Wang, Jialin; Zhang, Ziyuan; Ma, Shangqian; Jiang, Kang; Pan, Zhihua (Frontiers in Ecology and Evolution, 2022)
climatic threshold is critical to judge the impact and risk of climate change and proactively adapt agriculture. However, the climatic threshold of agriculture, especially crop production, remains unclear. To bridge this gap, taking winter wheat production from 1978 to 2017 in China as an example, this study clarified the definition of the climatic threshold of crop production and calculated it based on a mechanism model considering multiple factors and their synergies. The results showed that (1) the climate presented a warmer and wetter trend from 1978 to 2017, especially after 1996. (2) Water, fertilizer, and winter wheat yields increased significantly (22.4 mm/decade, 96.4 kg/ha·decade, and 674.2 kg/ha·decade, respectively, P<0.01). (3) The average optimal temperature and water thresholds for winter wheat were 7.3°C and 569 mm, respectively. The temperature rise was unfavorable for winter wheat production, and the water supply increase was beneficial to winter wheat production. (4) Increasing irrigation and fertilization could raise the optimal temperature threshold and adapt to climate warming in most provinces, while Shandong and Shaanxi both needed to reduce fertilization. We established a generalized method for calculating the climatic threshold of agricultural production and found that multifactor synergistic effects could influence the climatic threshold. The climatic threshold of winter wheat changed with different adaptation levels. However, considering the limitations in resource availability and environmental capacity, increasing the use efficiency of water and fertilizer is more important for adapting to climate change in the future.